The Effect of Current Account Saving, Net Interest Margin, and Credit Risk on Banking Probability - Juwita Ritna Satriyaningsih Juwita Ritna Satriyaningsih; Siti Aliyah (PT Syamilah Literasi Islami, 2024)
The purpose of this study is to identify the effect of the CASA (Current Account Saving Account), NIM (Net Interest Margin), and credit risk on banking profitability. This research method using secondary data obtained from the financial reports of banks that suitable with the sampel criteria found of the IDX (Indonesia Stock Exchange) for the 2018 to 2022 period. Samples were taken using the Purposive Sampling Method which was then processed with EViews 10 version program. Based on samples obtained are PT. Bank Negara Indonesia (Persero) Tbk., PT. Bank Rakyat Indonesia (Persero) Tbk., PT. Bank Mandiri (Persero) Tbk., and PT. Bank Tabungan Negara (Persero) Tbk. The results of this study indicate that partially, CASA (Current Account Saving Account) has no effect on banking profitability, NIM (Net Interest Margin) has a significant positive effect on banking profitability, and credit risk has a significant negative effect on banking profitability.